2008
DOI: 10.1002/jcb.21870
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear and nuclear envelope localization of dystrophin Dp71 and dystrophin‐associated proteins (DAPs) in the C2C12 muscle cells: DAPs nuclear localization is modulated during myogenesis

Abstract: Dystrophin and dystrophin-associated proteins (DAPs) form a complex around the sarcolemma, which gives stability to the sarcolemma and leads signal transduction. Recently, the nuclear presence of dystrophin Dp71 and DAPs has been revealed in different non-muscle cell types, opening the possibility that these proteins could also be present in the nucleus of muscle cells. In this study, we analyzed by Immunofluorescence assays and Immunoblotting analysis of cell fractions the subcellular localization of Dp71 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 41 publications
0
50
0
2
Order By: Relevance
“…Similarly, treatments with NO donors favor mitochondrial biogenesis and myogenesis and restore oxidative capacity in affected myocytes (71, 72). In conclusion, our results show that nNOS is anchored via the PDZ domain also at the Dystrophin-Syntrophin complex sited at the nuclear envelope of myocytes (58), and this event is mandatory for the NO/CREB/PGC-1␣-driven mitochondrial biogenesis. On the basis of our results, it is conceivable that the lack of nNOS anchoring to the nucleus may contribute to myopathy because of impaired mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Similarly, treatments with NO donors favor mitochondrial biogenesis and myogenesis and restore oxidative capacity in affected myocytes (71, 72). In conclusion, our results show that nNOS is anchored via the PDZ domain also at the Dystrophin-Syntrophin complex sited at the nuclear envelope of myocytes (58), and this event is mandatory for the NO/CREB/PGC-1␣-driven mitochondrial biogenesis. On the basis of our results, it is conceivable that the lack of nNOS anchoring to the nucleus may contribute to myopathy because of impaired mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 58%
“…However, ␣-Syntrophin and Dystrophin have been also observed in the inner nuclear membrane of cultured myocytes, and its level increases during myogenesis in nuclei (57,58). Interestingly, nNOS␣ has been revealed in the nuclear membrane of HeLa cells in association with Dystrophin and ␣-Syntrophin (46).…”
Section: Discussionmentioning
confidence: 99%
“…The nuclear DAPC is not cell-type specific, we have characterized similar complexes in the nucleus of HeLa [26] and C2C12 cells [27], which suggests an important unknown role for this complex in nuclear activities. We found that Dp71d as well as b-dystroglycan and b-dystrobrevin are associated with the nuclear matrix, a permanent network of core filaments underlying ticker fibers which is proposed to be the platform for numerous nuclear processes, including RNA processing, transcription regulation and DNA repair.…”
Section: Discussionmentioning
confidence: 95%
“…The presence of Dp71d and the dystrophin-associated proteins (DAPs) has been observed in the nuclei of HeLa and C2C12 cells [26,27]. Therefore, we decided to ascertain whether these proteins display nuclear localization in the PC12 neuronal cells.…”
Section: Subcellular Localization Of Dp71d and The Daps In The Pc12 Amentioning
confidence: 97%
“…The presence of Dp71 and some DGC elements that form a nuclear complex at the plasma membrane and in the nucleus of muscle cells suggested their participation in nuclear structure and in the modulation of nuclear processes [42].…”
Section: Dual Role Of the Dp71 Isoformmentioning
confidence: 99%